Гриф. Возвращение наемника - Приходько Олег Игоревич (Черная кошка, 1999)
Экземпляры: аб. ЦБ (20180917) / Инвентарный номер: 5157 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: П 77 / ББК: 84(2Рос=Рус)6